Optimizing jacket design for two-wheeler delivery workers during rainy conditions - Sujin Lim; Jisoo Ha (Journal of Engineered Fibers and Fabrics)
Work transactions through platforms enabled by digital transformation have exploded in the wake of COVID-19. Furthermore, the number of workers involved has increased rapidly. With the expansion of non-face-to-face communication even after the end of the pandemic, the transaction market value of delivery services is expected to reach USD 59.8 billion in 2022. The media has reported that transportation for delivery through delivery apps is mainly utilizing two-wheelers. Also riders to make as many deliveries as possible and receive good ratings, most work more than 8 h. This complex work environment and long working hours expose them to physical fatigue, scrapes, bumps, falls, and other accidents, making it more necessary than ever to pay attention to the health and safety of delivery riders. However, research on apparel design for delivery riders is limited. The clothing of delivery riders who work long hours influences their performance, comfort, and mobility. Recent field research suggests that delivery riders are unsatisfied with their current workwear, and ergonomic discomfort mainly affects their safety-critical work patterns and frequent physical movements. An urgent need exists to develop better designs that consider comfort and performance. This study serves as a resource for identifying and reflecting delivery riders’ needs and improvements to their workwear and providing good design. Recent field research suggests that delivery riders are unsatisfied with their current workwear, and ergonomic discomfort mainly affects their safety-critical work patterns and frequent physical movements. An urgent need exists to develop better designs that consider comfort and performance. This study serves as a resource for identifying and reflecting delivery riders’ needs and improvements to their workwear and providing good design.